(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the impact of using local shopping applications in the host country on the adaptation of Indonesian students studying abroad. The main focus is directed towards three dimensions of adaptation: social, cultural, and psychological. The use of local shopping applications such as Amazon, Taobao, Shopee, and similar ones has become part of the daily lives of students and has the potential to play an important role in supporting the adaptation process. The research method employed is associative quantitative, using a survey approach through online questionnaires. Respondents were Indonesian students in various higher education destination countries who had used local shopping applications for at least three months. Data analysis was conducted using multiple linear regression to test the relationship between the use of shopping applications and the three adaptation dimensions. The findings indicate that the use of local shopping applications has a significant impact on all three aspects of adaptation. In the social aspect, these applications facilitate indirect interaction with elements of the local society, broaden the understanding of service norms, and enhance the sense of social connectedness. From a cultural standpoint, the applications serve as digital showcases that expose students to local symbols, products, and cultural practices, thus enriching the acculturation process.